2017
DOI: 10.3389/fphar.2017.00939
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Ameliorates Inflammatory Responses by Inhibiting the TLR4-Mediated Pathway in Lipopolysaccharide-Induced Acute Lung Injury

Abstract: Acute lung injury (ALI) is a complex syndrome with sepsis occurring in critical patients, who usually lack effective therapy. Nuciferine is a primary bioactive component extracted from the lotus leaf, and it displays extensive pharmacological functions, including anti-cancer, anti-inflammatory, and antioxidant properties. Nevertheless, the effects of nuciferine on lipopolysaccharide (LPS)-stimulated ALI in mice has not been investigated. ALI of mice stimulated by LPS was used to determine the anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…Furthermore, recruitment of inflammatory cells contributes to increase of the alveolar-capillary barrier permeability and lung edema. Results of this study were in line with previous research [ 2 , 10 , 26 ], as LPS induced marked pulmonary edema presented by increased lung W/D ratio. The total protein content in the BALF, as another index of epithelial permeability and pulmonary edema [ 2 ], was highly increased in the BALF of mice exposed to LPS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, recruitment of inflammatory cells contributes to increase of the alveolar-capillary barrier permeability and lung edema. Results of this study were in line with previous research [ 2 , 10 , 26 ], as LPS induced marked pulmonary edema presented by increased lung W/D ratio. The total protein content in the BALF, as another index of epithelial permeability and pulmonary edema [ 2 ], was highly increased in the BALF of mice exposed to LPS.…”
Section: Discussionsupporting
confidence: 92%
“…LPS activates reactive oxygen species (ROS) generation and the release of proteases. Furthermore, LPS induces the activation of NF-κB signaling pathway and cytokine release [ 10 , 11 ]. Inflammatory mediators activate overproduction of ROS, leading to more oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of phytochemicals derived from natural plant have anti-inflammatory effects, such as phenolics, terpenolids, and alkaloids [ 19 ]. Nuciferine, an alkaloid found in the lotus leaves, exerted a protective effect against inflammation, in vivo [ 20 ] and in vitro [ 21 ]. Our results showed that nuciferine decreased the expression of inflammatory cytokines IL-6 and TNFα, in both protein and gene levels, dose dependently, in the LPS-treated RAW264.7 cells, indicating that nuciferine had potential anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TNFAIP3 may stabilize the endothelial barrier by regulating the expression of VE-cadherin in acute lung injury (ALI) (Soni et al, 2018 ). Previous studies have also indicated that endothelial cells-expressed TLR4 increased vascular permeability and inflammatory responses in the early stages of ALI and/or ARDS (Tauseef et al, 2012 ; Wu et al, 2017 ; Peng et al, 2019 ). Its mechanism of action was likely to be that TLR4 induced the immune response by activating NF-κB signaling pathway via phosphorylating IRAK1 and IRAK2.…”
Section: Discussionmentioning
confidence: 94%